2010
DOI: 10.1021/la100330c
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interaction Energies in the Behavior of Mixed Surfactant Systems: A Lattice Monte Carlo Simulation

Abstract: We have investigated micellization in systems containing two surfactant molecules with the same structure using a lattice Monte Carlo simulation method. For the binary systems containing two surfactants, we have varied the head-head interactions or tail-tail repulsions in order to mimic the nonideal behavior of mixed surfactant systems and to manipulate the net interactions between surfactant molecules. The simulation results indicate that interactions between headgroups or tailgroups have an effect on thermod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…[1][2][3][4][5][6][7]. Considerable studies have shown that the mixed surfactant systems often have better performance than mono surfactant systems from both physicochemical perspective and the point of view of application, and the study about the synergistic effects of mixed surfactants is drawing more and more attentions [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7]. Considerable studies have shown that the mixed surfactant systems often have better performance than mono surfactant systems from both physicochemical perspective and the point of view of application, and the study about the synergistic effects of mixed surfactants is drawing more and more attentions [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…When the measured conductivity of the solution is plotted as a function of total surfactant concentration, two different straight lines with different slopes are obtained. The intercept of these lines is taken as the critical micelle concentration (CMC) and the slope ratio allows the counterion binding constant B value to be determined [10][11][12][13].…”
Section: Apparatus and Methodsmentioning
confidence: 99%
“…Subsequently, the adaptation of regular solution theory, where the departure from the ideal is parameterized by a single interaction parameter (b), has formed the basis of the theoretical study of mixed surfactant solutions [10][11][12][13]. In this work, we present studies on the micellization of mixtures of sodium dodecylbenzenesulfonate with polyoxyethylene(4) lauryl ether (DBS/POLE4) as well as with polyoxyethylene(23) lauryl ether (DBS/POLOE23) in aqueous solution, eventually containing n-butanol (0, 0.1, and 0.2 M).…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental studies have been carried out using a variety of techniques on the micellization of mixed surfactant systems. The ideal solution approach has been used to interpret the properties of mixed micellar system and the adaptation of regular solution theory, where the departure from the ideal is calculated by a single interaction parameter (β), thus has put the foundation of the theoretical study of mixed surfactant solutions [158][159][160][161].…”
Section: Surfactant-surfactant Interactionsmentioning
confidence: 99%